A 26-Year-Old Male with Post-Traumatic Cephalgia: Case Report - Asy'hari, Mohammmad Alif; Rahmawati, Rahmawati; Santoso, Arif; Anggita, Dwi; Mustafa, Maulana Saggaf (Journal La Medihealtico, 2025)
Post-Traumatic Headaches (PTH) is the most frequent complaint after Traumatic Brain Injury (TBI). According to ICHD-3 Post-Traumatic Headaches (PTH) is the most common secondary headache disorder, accounting for around 4% of all headache symptoms that begin in 7 days after head injury, craniotomy or post-traumatic awareness. The main risk factors for PTH include a history of migraines or headaches, female gender, younger age, more severe head injury, and concurrent psychological symptoms, such as anxiety and depression. The clinical profile of PTH varies based on headache onset, duration, and severity. Pharmacological treatment often consists of analgesics and nonsteroidal anti-inflammatory drugs, tricyclic antidepressants, or antiepileptic drugs. PTH treatment has two components: acute treatment and prophylaxis. Analgesics (nonsteroidal anti-inflammatory drugs [NSAIDs]) or certain anti-headache medications (triptans) are used for acute treatment.